2013
DOI: 10.1001/jamainternmed.2013.6163
|View full text |Cite
|
Sign up to set email alerts
|

The Energy Content of Restaurant Foods Without Stated Calorie Information

Abstract: National recommendations emphasize self‐monitoring for prevention and treatment of obesity; however, little information is available on the dietary energy contents of meals obtained from non‐chain restaurants, which account for ≈50% of restaurants in the US. Using bomb calorimetry, we determined gross energy of the 42 most popular meals from 34 randomly selected restaurants in the 9 most common ethnic restaurant categories in Massachusetts. Mean energy of the 158 meals was 1327 kcal (95% CI, 1248–1406 kcal), e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
0
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 25 publications
4
32
0
2
Order By: Relevance
“…This reinforces the idea that the problem of obesity is eating at chain restaurants (most of which are fast-food establishments) when the problem is eating too many calories. This point is well made by Urban et al 3 in an article in this issue of the journal. They tested the energy content of meals from 9 common individual or small chain restaurants.…”
Section: Labeling Regulationssupporting
confidence: 62%
“…This reinforces the idea that the problem of obesity is eating at chain restaurants (most of which are fast-food establishments) when the problem is eating too many calories. This point is well made by Urban et al 3 in an article in this issue of the journal. They tested the energy content of meals from 9 common individual or small chain restaurants.…”
Section: Labeling Regulationssupporting
confidence: 62%
“…The mean price for a meal in an FSR was $9.95 (http://www.ers.usda.gov); dividing this price by the state-level values of the total annual expenditure in FSRs gave the mean number of meals per year consumed at FSRs in each state. The energy obtained from a typical meal (entrée plus sides) in an FSR in the United States is w1327.0 kcal (5552 kJ) (44).…”
Section: Covariatesmentioning
confidence: 99%
“…Moreover, in the absence of data to the contrary, we had to assume that the portion sizes and pricing at these 5 outlets were uniform across the 48 states. For FSRs, we used the energy content of a typical meal (entrée plus sides) based on a study in Boston that suggested a mean meal energy content of 1327 kcal (44). A more recent survey that included a more nationally representative sampling suggested a lower figure of 1205 kcal (47).…”
Section: Sensitivity Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…A typical fast food meal contains more than 800 calories, 12 which for most adults exceeds 30% of their daily calorie needs (ie, if a person ate 3 times a day and required 1800 to 2000 calories a day, they would consume 400 to 600 extra calories because they did not adjust their later intake). 13 For example, a study of adolescents found that when they ate fast food, they did not compensate for the excess calories later in the day and had a net increase in calories, saturated fat, and sugar compared with days that they did not eat fast food meals. 14 Gerend 6 found that both male and female college students ordered fast food meals that were in excess of 900 calories when they ordered from an online menu.…”
mentioning
confidence: 99%